2008
DOI: 10.1016/s1472-6483(10)60198-8
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst culture and transfer: lessons from an unselected, difficult IVF population

Abstract: Blastocyst-stage transfer has yielded excellent results in good prognosis IVF patients, but its efficacy in the general IVF population has not been clearly demonstrated. The objective of this study was to compare cleavage-stage and blastocyst-stage transfer in a mixed, general IVF population. In a prospective, quasi-randomized study, 152 patients underwent 164 treatment cycles. Patients were allocated to cleavage-stage (group 1; n = 94) or blastocyst-stage (group 2; n = 70) transfer. Main outcome measures incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…These findings are consistent with another recent study [15], which also reported that blastocyst culture and transfer reduced implantation and pregnancy rates in the general ART patient population compared to cleavage-stage embryo transfer. Nevertheless, positive results of blastocyst transfer have been reported by many previous studies, which all revealed higher implantation and pregnancy rates with blastocyst transfer compared to cleavage-stage embryo transfer [16-20].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with another recent study [15], which also reported that blastocyst culture and transfer reduced implantation and pregnancy rates in the general ART patient population compared to cleavage-stage embryo transfer. Nevertheless, positive results of blastocyst transfer have been reported by many previous studies, which all revealed higher implantation and pregnancy rates with blastocyst transfer compared to cleavage-stage embryo transfer [16-20].…”
Section: Discussionsupporting
confidence: 93%
“…We noted earlier that eSET produces lower birth rates than two-embryo transfers [ 26 , 27 ]; but eSET is also convincingly associated with declining multiple pregnancies (Table 1 ). Losses in birthrates with eSET can be compensated for by an additional thaw cycle [ 26 , 27 ]. Those compensatory births, however, do not appear in the CDC’s ASRs of fndIVF cycles.…”
Section: Resultsmentioning
confidence: 65%
“…No significant difference in demographic data was found between them, but the number of repeated implantation failure (RIF) was significantly higher in A (P= 0.027) than B. Also, comparisons of follicles number by U/S after stimulation cycle and before OPU showed that significant differences were noticed in number of follicles with size of (15)(16)(17) mm in B and P= 0.022. A high number of oocytes retrieved was noticed in B (12.41+5.82) than A (10.57+6.02), while the number of abnormal oocytes retrieved from patients of A were more (1.25+1.75) than those retrieved from patients of B (1.15+1.59), but not significant.…”
Section: Resultsmentioning
confidence: 88%
“…Studies that follow up PRs after continual ICSI attempts showed that the possibility of pregnancy per cycle tends to be stabilized in the first three attempts, and then it declines afterwards. Some specialists considered that after each failed trial, the PRs in subsequent trial decrease by as much as 57%, but the most remarkable decrease is noticed after the third trial (16,17) . The stimulation data of all patients who entered COH were compared (table1).…”
Section: Discussionmentioning
confidence: 99%